THE IMPACT OF TURKISH CULTURE ON UZBEK PEOPLE - Toshpulatova Sarvinoz; Nurova Maftuna (TADQIQOTLAR, 2025)
Annotation:  This  article  talks  almost  how  Turkish  culture  has  affected  the conventions,  dialect,  instruction,  design,  and  existence  of  Uzbek  individuals.  It examines the authentic foundation and the part of media, instruction, and tourism. The article too appears how youthful individuals in Uzbekistan are interfacing with Turkish patterns and values.